Behavioral Economics and Framing Effects in Guilty Pleas: A Defendant Decision Making Experiment. (23rd February 2021) - Garnier-Dykstra, Laura M.; Wilson, Theodore
Abstract: With over 90% of convictions resulting from guilty pleas, it is of great importance to examine factors influencing the likelihood of plea acceptance. Prior research suggests individuals are risk-seeking in the domain of losses, prompting questions related to why potentially innocent defendants would plead guilty. Birke suggests defendants may view pleas as a gain, making them more risk-averse. The current study uses an experiment to explore how the framing of a plea bargain impacts the likelihood of plea acceptance. Undergraduate criminal justice students ( n = 501) were presented with two plea bargaining scenarios with the guilty plea randomly assigned to be framed as a gain, loss, or neutral. Results indicate that framing a plea as a gain (as compared to neutral or loss) induces the innocent and discourages the guilty to plead guilty across every appraised subgroup based on individual-level factors. Implications for future research and defendant decision-making are discussed.